Needs of the older adult population in dental care, Universidad of Costa Rica - Amador Cedeño, Mario (2019)
This document presents the results of a study which purpose was to identify the needs of dental care that the elderly population has in the Clinic of Restorative Sciences of the Faculty of Dentistry of the University of Costa Rica. The research was developed with a qualitative approach and a mixed design. A group session was held with students and professors from the Faculty of Dentistry and surveys were applied to older adults, users of the dental services. The Atlas ti7® program was used to analyze the data. Among the main results obtained, the need for induction of dental staff in gerontology issues is confirmed; as well, improvements in spaces and the quality of care given in the Restorative Sciences Clinic